A woman from Łódź in Podlasie. Landscape and still life by Agnieszka Żmuda - Sienkiewicz, Jan Wiktor (Ars inspiratio: Studies dedicated to Professor Eleonora Jedlińska, 2024)
Agnieszka Żmuda is a painter originally from Lodz who has been working in Białystok for more than twenty years. She showed her paintings for the first time in an individual exhibition at the Alfons Karny Museum in Białystok in late 2023. The text is the first attempt to look at this artist’s creative achievements to date. She received her academic training in painting at the Academy of Fine Arts in Warsaw, and crowned it with a Master of Fine Arts degree obtained with distinction in 2001. Working in tempera and oil techniques, she primarily focuses on landscapes and still life genres. In her diverse and experimental painting, we can find many vectors and directions that particularly draw from the tradition of Polish colorism, born in the 1930s. This tradition was further developed and present in post-war academic teaching in Kraków and Warsaw artistic circles. The workshop experiences from Żmuda’s studies, acquired at the Warsaw Academy of Fine Arts under the guidance of Danuta Makowska (a student of the Kapist masters), have had a significant impact on the search for her own artistic path. Color and composition are the main axes of Żmuda’s exploration in painting, which is diverse and full of experiments. It is constantly evolving: from realistic compositions to increasingly abstract and expressionistic ones, demonstrating a conscious development combined with freshness of expression.